Strategy of the Takmir of the Great Mosque of the Cubadak Market: Recording and Accountability of Sharia Finances - Bagas Aulia; Kamilah, K.; Yenni Samri Juliati Nasution (Universitas KH. Abdul Chalim Mojokerto, 2025)
Mosques are non-profit institutions that focus on religious activities, so it is important to have a reliable accounting system in the management of public funds to maintain transparency and accountability. However, mosque management often only records general receipts and expenditures without clear details of their sources and purposes, which can raise public suspicion. This study aims to evaluate how Takmir Raya Pasar Cubadak conducts its financial recording and financial reporting responsibilities. The results show that the mosque's financial management is still far from PSAK 109 and ISAK 35 standards, especially in terms of transparency and separation of funds such as zakat, infaq, and sadaqah. The current financial records only include incoming and outgoing cash without details of the source and allocation of funds, which results in financial accountability not meeting the expected standards. Therefore, financial management at the Cubadak Market Grand Mosque needs to be improved to be better and following applicable accounting principles.